PENGARUH LATIHAN KOMBINASI PASSING TRIANGLE DAN QUADRANGLE TERHADAP KUALITAS PASSING PEMAIN SEPAK BOLA U-17 TARUNA GOMONG FC - Irawan, Dedy; Elya Wibawa S. (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2026)
This study aimed to compare the effects of triangle passing and quadrangle passing drills on the passing quality of U-17 Taruna Gomong FC football players. The study employed a quantitative approach with a quasi-experimental two-group pretest-posttest design. The population consisted of 24 players, and 16 players who met the inclusion criteria were selected through purposive sampling. The sample was then divided into two equal groups using ordinal pairing based on pretest scores. Group A received triangle passing training, whereas Group B received quadrangle passing training for 18 sessions over six weeks. The instrument used was a 30-second passing and ball-control test adapted from Nurhasan. Data were analyzed using the Shapiro-Wilk normality test, homogeneity test, paired-sample t-test, and independent-sample t-test at a significance level of 0.05. The results showed that triangle passing training significantly improved passing quality (t = 10.58; p = 0.000) with a 15.38% increase. Quadrangle passing training also significantly improved passing quality (t = 5.36; p = 0.001) with a 12.75% increase. However, the difference between the two training methods was not statistically significant (t = 2.030; p = 0.062). These findings indicate that both drills can be used to improve players’ passing quality, although neither method was statistically superior.